2005
DOI: 10.1089/jpm.2005.8.1196
|View full text |Cite
|
Sign up to set email alerts
|

Operational and Financial Performance of Publicly Traded Hospice Companies

Abstract: Results suggest publicly traded for-profit hospices, in comparison to for-profit and nonprofit hospices, are able to earn substantially higher profits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Although it is not known if patient and family choice between hospices is associated with higher quality care for patients and families, there is mounting evidence that hospices vary nationally in program structure [19][20][21][22][23] and patient care. [24][25][26][27][28][29][30] Future studies regarding the extent to which having greater choice between hospices improves a family's ability to find a hospice that meets their needs and the potential linkage between hospice choice and hospice quality of care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not known if patient and family choice between hospices is associated with higher quality care for patients and families, there is mounting evidence that hospices vary nationally in program structure [19][20][21][22][23] and patient care. [24][25][26][27][28][29][30] Future studies regarding the extent to which having greater choice between hospices improves a family's ability to find a hospice that meets their needs and the potential linkage between hospice choice and hospice quality of care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate factors that could drive differences beyond profit status alone, prior studies have analyzed the impact of agency size and tenure in the marketplace, for instance finding that smaller and newer for-profit agencies have higher rates of live discharge and longer lengths of stay than other agencies. (11, 13, 14) Few analyses of hospice care have explored the role of the agencies’ parent companies. Analyses based on a national survey of hospice agencies included chain status as a control variable in examining for-profit vs. not-for-profit differences in enrollment practices and the provision of community benefits; (4, 15) another article using the same dataset examined the influence of chain status on self-reported care practices, finding that chain agencies (the article did not distinguish between for-profit and not-for-profit chains) generally offered higher quality of care relative to non-chains.…”
Section: Introductionmentioning
confidence: 99%
“…6 A recent study found that higher revenues have contributed to higher profitability for publicly traded hospices. 7 The median profit margin in 2003 for large hospices owned by publicly traded companies was 18.2% compared to a median value of only 2.2% for nonprofit hospices. 7 As a result of this growth in earnings, these companies have been able to access the capital markets to fund their acquisition of existing not-for-profit community hospices and/or the development of new hospices.…”
mentioning
confidence: 97%
“…7 The median profit margin in 2003 for large hospices owned by publicly traded companies was 18.2% compared to a median value of only 2.2% for nonprofit hospices. 7 As a result of this growth in earnings, these companies have been able to access the capital markets to fund their acquisition of existing not-for-profit community hospices and/or the development of new hospices. 8 The operational performance of hospices has become a topic of interest recently in the health care and management literature due to the widespread growth of hospices and the growing acceptance of hospices by providers and the public.…”
mentioning
confidence: 97%